The Theta Rhythm of the Hippocampus: From Neuronal and Circuit Mechanisms to Behavior - Nuñez, Angel; Buño, Washington (Frontiers in Cellular Neuroscience, 2021)
This review focuses on the neuronal and circuit mechanisms involved in the generation of the theta () rhythm and of its participation in behavior. Data has accumulted indicating that  arises from interactions between medial septum-diagonal band of Broca (MS-DbB) and intra-hippocampal circuits. The intrinsic properties of MS-DbB and hippocampal neurons have also been shown to play a key role in  generation. A growing number of studies suggest that  may represent a timing mechanism to temporally organize movement sequences, memory encoding, or planned trajectories for spatial navigation. To accomplish those functions  and gamma () oscillations interact during the awake state and REM sleep, which are considered to be critical for learning and memory processes. Further, we discuss that the loss of this interaction is at the base of various neurophatological conditions.